Decadal Prediction of Marine Heatwaves in MPI‐ESM - Hövel, Laura; Brune, Sebastian; Baehr, Johanna; Brune, Sebastian; 1 Center for Earth System Research and Sustainability Institute of Oceanography Universität Hamburg Hamburg Germany; Baehr, Johanna; 1 Center for Earth System Research and Sustainability Institute of Oceanography Universität Hamburg Hamburg Germany (Geophysical Research Letters, 2022)
Marine Heatwaves (MHW) are SST extremes that can have devastating impacts on marine ecosystems and can influence circulation patterns in the ocean and the atmosphere. Here, we present a first attempt to study the decadal predictability of MHW in an ensemble of decadal hindcasts based on the Max Planck Institute Earth System Model. For the global mean we find significant skill for the multiyear MHW trends but we cannot predict the interannual to decadal variability of MHW. In the Subpolar North Atlantic, we can predict the interannual to decadal variability of MHW days and frequency up to lead year 8. We demonstrate that in the Subpolar North Atlantic, any increase in SST is accompanied by more MHW and vice versa. Thereby we gain additional information about the decadal evolution of SST that go beyond predicting the yearly mean SST. Plain Language Summary: Marine Heatwaves (MHW) are periods with extremely warm ocean temperatures that can be disruptive for many marine ecosystems. Here, we provide an attempt to predict the evolution of MHW in the global ocean for the following two to ten years. With this analysis we improve our understanding of the predictability of surface temperatures in the global ocean. We find that there are strong regional differences in the predictability of MHW. One region where MHW can be predicted successfully is the Subpolar North Atlantic. We show that an increase in mean ocean temperature also results in an increase in MHW. Key Points: Global mean multiyear trends for Marine Heatwaves (MHW) days and frequency can be skillfully predicted for the following two to eight years. In the Subpolar North Atlantic, yearly characteristics MHW days and frequency are predictable up to leadyear eight. Any increase in SST in the Subpolar North Atlantic is accompanied by an increase in MHW and vice versa. Copernicus Climate Change Service Deutsche Forschungsgemeinschaft http://hdl.handle.net/hdl:21.14106/f2fdc61b13828ed5284f4e4ab41e63f8a84c6e52